2018
DOI: 10.1038/s41598-018-36438-5
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial distribution of under-five mortality and factors associated with multiple cases of under-five deaths within a family in the rural area of Khuzestan, Southern Iran

Abstract: Under-five mortality (U5M) is an important indicator of the overall health and development of society. There is a wide gap in U5M among different countries and also within the countries. This study was carried out to assess the prevalence, as well as the socio-demographic, and health-related causes of U5M in the region of study. A cross-sectional study was conducted among all registered cases of U5M in rural areas of Khuzestan province, Iran, during the years 2011 to 2015. To assess the socio-demographic deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…(26-28) In the same way, Malderen et al, (29) reported that U5M in Sub-Saharan Africa was strongly affected by socioeconomic status like child sex, maternal education, household wealth, and residency. Similar GIS-based study was conducted by, Anafcheh et al, (30) in Iran to determine the spatial distribution of U5M in Khuzestan province. They concluded that there was a great disparity of U5M a cross the province.…”
Section: Discussionmentioning
confidence: 80%
“…(26-28) In the same way, Malderen et al, (29) reported that U5M in Sub-Saharan Africa was strongly affected by socioeconomic status like child sex, maternal education, household wealth, and residency. Similar GIS-based study was conducted by, Anafcheh et al, (30) in Iran to determine the spatial distribution of U5M in Khuzestan province. They concluded that there was a great disparity of U5M a cross the province.…”
Section: Discussionmentioning
confidence: 80%
“…Mother's age was the key factor associated with UFM in Bhutan (Dendup et al, 2018). Multivariate analysis showed that having >1 under-5 child death was associated with maternal age at delivery (<18 or >35) of mothers in a study conducted in Iran (Anafcheh et al, 2018). Compared to those born to younger (≤25 years) mothers, children born to mothers aged 36-40 years, 41-45 years, and more than 45 years had signi cantly lower odds of UFM (Dendup et al, 2018).…”
Section: Mother's Agementioning
confidence: 93%
“…(Dendup et al, 2018). Multivariate analysis showed that having >1 under-5 child death was associated with maternal age at delivery (<18 or >35) of mothers in a study conducted in Iran (Anafcheh et al, 2018). Compared to those born to younger (≤25 years) mothers, children born to mothers aged 36-40 years, 41-45 years, and more than 45 years had signi cantly lower odds of UFM (Dendup et al, 2018).…”
Section: Colostrum Feedingmentioning
confidence: 94%